The Impact of Bailout on Financial Performance And Bank Risk-Taking During Financial Crisis: A Critical Systematic Review - Dety Nurfadilah (International Journal of Business Studies, 2019)
The focus on the bank bailout has been increased since the global financial crisis in 2008 in most countries. However, previous studies often discover the relationship between bailout and corporate governance. In this study, bank bailout literature will be reviewed with the focus on the impact of bailout on bank financial performance and bank risk-taking during the financial crisis. Multi-step strategy is used to collect the data from 2000 to 2016. From the 7 papers were chosen based on the criteria. This systematic review has shown that the bank bailout has a positive impact on financial performance, however, it has a negative impact on bank risk-taking for a longer period.